RUMAH PESONA DESA SIDOREKSO:: Program Penguatan Moderasi Beragama - Fadlullah Hana, Kharis; Indriani, Sholikah; F Aulia, Alis (Proceedings of Annual Conference on Community Engagement, 2023)
Radicalism and Liberalism in Indonesia are issues that currently need attention. Villagers who do not understand religion comprehensively are easily directed to it. It causes tolerance to fade even more. Some villages in Kaliwungu sub-district are unaware that they have ever found their people affiliated with the Radicalism network. This Community Service Program aims to provide education and development of community potential based on religious moderation. The goal is to form a society that has a spirit of development based on a moderate understanding of religion. This service method uses ABCD (Asset Based Community Development). Lecturers and students together with the community map the potential that exists in the village and develop it based on moderate religious views. The results of this service have been carried out village potential data collection programs, potential assistance and socialization of religious moderation. Outpunya has been made Sidorekso Village Enchantment House by displaying the Village Potential in it and moderate Religious Understanding. The results have also been documented in the form of books distributed to the Society.